2015
DOI: 10.3390/md13042105
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin Attenuates Early Acute Kidney Injury Following Severe Burns in Rats by Ameliorating Oxidative Stress and Mitochondrial-Related Apoptosis

Abstract: Early acute kidney injury (AKI) is a devastating complication in critical burn patients, and it is associated with severe morbidity and mortality. The mechanism of AKI is multifactorial. Astaxanthin (ATX) is a natural compound that is widely distributed in marine organisms; it is a strong antioxidant and exhibits other biological effects that have been well studied in various traumatic injuries and diseases. Hence, we attempted to explore the potential protection of ATX against early post burn AKI and its poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
75
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(76 citation statements)
references
References 63 publications
0
75
0
1
Order By: Relevance
“…AKT is a key downstream effector of PI3K and is down-regulated in various cancers, including osteosarcoma and prostate cancer [31]. Previous studies have demonstrated that Akt inactivation might inhibit the expression of proteins associated with events that mediate the cancer development and progression, including apoptosis and cell cycle progression [29, 32, 33]. In our study, the results of the western blot analysis demonstrated that casticin significantly decreased p-Akt expression and that this effect was accompanied by an increase in p27.…”
Section: Resultsmentioning
confidence: 99%
“…AKT is a key downstream effector of PI3K and is down-regulated in various cancers, including osteosarcoma and prostate cancer [31]. Previous studies have demonstrated that Akt inactivation might inhibit the expression of proteins associated with events that mediate the cancer development and progression, including apoptosis and cell cycle progression [29, 32, 33]. In our study, the results of the western blot analysis demonstrated that casticin significantly decreased p-Akt expression and that this effect was accompanied by an increase in p27.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, several studies have examined this p38 pathway even further while simultaneously elucidating additional molecular mechanisms. For example, Guo et al showed that serum creatinine levels tripled after 40%TBSA scald injury in rats, which was reduced with the anti-oxidant astaxanthin [110]. This anti-oxidant partially blocked lipid peroxidation (MDA) and restored levels of SOD and catalase, while preventing apoptosis.…”
Section: Accepted Manuscriptmentioning
confidence: 94%
“…effect 34,35 . Studies have shown that the protective effects of astaxanthin against many kidney diseases is related to antiapoptosis 3,4,36 . Considering the crucial role of oxidative stress in inducing pathological changes of IR and the antioxidant properties of ATX, ATX might alleviate tubular necrosis/ apoptosis and inflammation via scavenging free radical 19 .…”
Section: Anti-apoptosis Effectsmentioning
confidence: 99%
“…Many studies have proven that astaxanthin has a preventive effect on various kidney diseases [1][2][3][4][5] . Oxidative stress and apoptosis are common pathophysiological features of contrast agent induced acute kidney injury (CI-AKI), hence ATX may have a potential therapeutic role in this condition.…”
Section: Introductionmentioning
confidence: 99%